Factors affecting millennials' intentions to consume local and foreign media in Singapore - Lee, Daphne (2018)
This study examines the effects of local-global identity and consumer-cultural nationalism on local and foreign entertainment media use intentions of Singaporean millennials. In our study, the theory of planned behaviour is used as a theoretical foundation accounting for media use intentions. Regression analysis of Singaporean millennials (N = 1,020) indicated that local identity and consumer-cultural nationalism were positively associated with intentions to consume local media. In addition, global identity was positively associated with foreign media use intentions. Findings suggest importance of individual-level variables in determining preference for local and foreign entertainment media.